Back Cover: Protection of Platinum‐Based Micromotors from Thiol Toxicity by Using Manganese Oxide (Chem. Eur. J. 34/2017). Issue 34 (25th April 2017) - Minh, Tam Do; Safdar, Muhammad; Jänis, Janne
Abstract : Keep it moving : A proof‐of‐concept solution for the protection of Pt‐based micromotors against thiol‐induced deactivation, which limits their functionalization by gold–thiol chemistry for a variety of applications, is proposed. Thiols are known to bind to the Pt surface, which can lead to serious deactivation of the catalyst. The inner catalytic surface of the electrochemically fabricated Au/Pt micromotors can be covered with MnO2 to completely block the pores prior to thiol treatment, thus protecting the inner Pt surface from thiol chemisorption. This approach will greatly facilitate the use of the functionalized Pt micromotors for which the thiol toxicity has been a limiting factor. More information can be found in the Communication by J. Jänis et al. onpage 8134 .